The effects of compensation and board quality on non-GAAP disclosures in Europe - Isidro, H. (2016)
This study reports international evidence on the impact of compensation and board quality on the voluntary disclosure of non-GAAP earnings numbers. We find that compensation contracts of board directors that are linked to firm's market performance are associated with a higher probability of disclosure of non-GAAP figures in the earnings announcements' press release. Furthermore, when this type of compensation is used, firms tend to report non-GAAP figures in the title of the press release, make more adjustments for recurring items, and avoid reporting reconciliations. These reporting practices have been associated with opportunistic disclosure. We also show that an efficient governance structure of the board of directors can help restrain most of these discretionary disclosure decisions regarding non-GAAP reporting